Regenerated polypropylene composite material as well as preparation method and application thereof
By adding nanoporous silicate, toughening/transparent agent and anti-precipitation agent to regenerated polypropylene, the problems of poor toughness, low transparency, high odor and poor dissolution content are solved, and high transparency and low odor are achieved , low-soluble and high-tough recycled polypropylene composite materials, suitable for food packaging and other fields.
Patent Information
- Application Number
- CN202411670723.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing recycled polypropylene materials have problems such as poor toughness, low transparency, high odor and inadequate slurry content in food packaging, and it is difficult to meet the requirements of low odor, transparency and slurry content control at the same time.
By adding nanoporous silicates, toughening/transparent agents and anti-precipitation agents to regenerated polypropylene, the composition and processing process of the material are optimized, and the adsorption performance, toughness and transparency of the material are improved while reducing dissolving and odor.
It achieves high transparency, low odor, low dissolving and high toughness of recycled polypropylene composite materials, meeting strict standards for food packaging, pharmaceutical packaging and tableware.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a recycled polypropylene composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the Internet of Things, the efficiency of commodity circulation continues to improve. A huge amount of product packaging flows around the world with commodities, which has caused serious pressure on environmental and ecological protection. Plastics are an indispensable material for logistics packaging due to their low density, good light transmittance, low precipitation, and easy molding, and they are growing rapidly with the development of the logistics industry. In such a market context, many scholars and experts have proposed the concept of circular economy to deal with environmental damage. This new environmental concept is based on the existing resource consumption mode to achieve the goal of reusing resources, increasing product added value, reducing energy consumption, and reducing environmental pollution.
[0003] In order to effectively recycle food-grade packaging materials, specific plans and control methods for challenge testing of recycled materials are proposed. Recycled materials that can pass the challenge test can be used for food packaging in certain occasions. It is necessary to meet the requirements of low odor, transparency, and control of soluble content (tested in accordance with FDA 21CFR 177.1520 standard) in the fields of food, medical packaging, and tableware.
[0004] At the same time, the toughness of recycled polypropylene is poor, so a toughening agent needs to be added, and the addition of a toughening agent will affect the transparency and the content of dissolved matter. Therefore, it is a great challenge to simultaneously obtain a recycled polypropylene composite material with good toughness, high transparency, low odor, and content control of dissolved matter. Summary of the invention
[0005] The object of the present invention is to provide a recycled polypropylene composite material with high transparency, low odor, satisfactory dissolution content control and good toughness, and a preparation method and application thereof.
[0006] The present invention is achieved through the following technical solutions: A recycled polypropylene composite material comprises the following components in parts by weight: Recycled polypropylene 90-97 parts; Nanoporous silicate 0.3-0.8 parts; 3-8 parts of toughening / transparent agent; Anti-precipitation agent 0.05-0.2 parts; The specific surface area of nanoporous silicates is 1000-10000m 2 / g, D50 particle size is 10-50 nanometers; The anti-precipitation agent is selected from bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate.
[0007] Compared with the inorganic silicates with traditional porous structures, the nanoporous silicates capable of achieving the purpose of the present invention have a larger comparative area, which makes them have stronger adsorption performance and smaller particle size. They can effectively adsorb small molecules and act as a good nucleating agent, refining the size of polypropylene crystals and improving transparency.
[0008] The toughening / transparent agent is selected from at least one of ethylene-octene copolymer (POE), olefin block copolymer (INFUSE), and styrene-ethylene-butylene-styrene block copolymer (SEBS); preferably, the toughening / transparent agent is selected from styrene-ethylene-butylene-styrene block copolymer.
[0009] Optionally, the commercially available ethylene-octene copolymer has the following grades: POE 8842, Dow Chemical; Optionally, the commercially available olefin block copolymers are POE LC168, LG Chemical, and POE ENGAGE 7467, Dow Chemical.
[0010] Optionally, the commercially available styrene-ethylene-butylene-styrene block copolymer has the following grades: SEBS 7551, Li Changrong, or Y-501T, Baling Petrochemical.
[0011] The specific surface area test method of nanoporous silicate is: using an inert gas adsorption method to test the specific surface area; the D50 test method is using a laser particle size distribution analyzer to test the D50 particle size.
[0012] It is possible to choose whether to add 0-2 parts of processing aids according to actual conditions. The processing aids are selected from at least one of antioxidants, lubricants, ultraviolet absorbers, and pigments.
[0013] The antioxidant may be: 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; 2,5-di-tert-butyl-4-hydroxybenzyl dimethylamine; diethyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; stearyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; 3,5-di-tert-butyl-4-hydroxyphenyl-3,5-distearyl-thiotriazolylamine; 2,6-di-tert-butyl-4-hydroxymethylphenol; 2,4-di-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylglycerol allyl ether)-1,3,5-triazine; N,N'-hexamethylenebis( 3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid); N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; triethylene glycol-bis[3-(3,5-dimethyl-4-hydroxyphenyl)propionate]; triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]; 2,2'-thiodiethyl-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc.
[0014] The lubricant may be: at least one of stearate lubricants, fatty acid lubricants, and stearate ester lubricants; the stearate lubricant is selected from at least one of calcium stearate, magnesium stearate, and zinc stearate; the fatty acid lubricant is selected from at least one of fatty acids, fatty acid derivatives, and fatty acid esters; the stearate ester lubricant is selected from at least one of pentaerythritol stearate.
[0015] The light transmittance (2mm) of the recycled polypropylene raw material used in the present invention is greater than 70%.
[0016] The recycled polypropylene composite material of the present invention is tested on particles with reference to the non-cooking standard in FDA 21CFR 177.1520, with the maximum dissolution in n-hexane being less than 4.0%, the maximum dissolution in xylene being less than 23%, the volatile matter test being less than 0.1%, the light transmittance being greater than 70% (2 mm), and the haze being less than 50% (2 mm), thus being able to meet the requirements for food packaging, pharmaceutical packaging, and tableware.
[0017] The test method for light transmittance is: use a visible light spectrometer to test the light transmittance of a 2mm thick square plate.
[0018] The preparation method of the recycled polypropylene composite material of the present invention comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder, with the screw temperature ranging from 180 to 230° C., to obtain the recycled polypropylene composite material.
[0019] The recycled polypropylene composite material of the invention is used for preparing food packaging, medicine packaging and tableware.
[0020] The present invention has the following beneficial effects: The invention can effectively absorb the odor of recycled polypropylene and reduce the dissolution by adding nanoporous silicate with specific parameters, but will not significantly reduce the transparency; at the same time, the anti-precipitation agent can improve the formation of impurities in the processing process and the precipitation of impurities on the surface, thereby significantly reducing the haze and improving the light transmittance; further, by selecting a toughening / transparent agent, not only the toughness can be improved, but also the transparency of the recycled polypropylene composite material can be improved, and compared with other types of toughening agents, the xylene dissolution can be further reduced. The recycled polypropylene composite material of the invention has the advantages of qualified dissolution detection, high transparency, low odor and good toughness. DETAILED DESCRIPTION
[0021] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0022] Recycled polypropylene 1: Recycled from transparent bottle caps, after sorting, crushing, friction cleaning, drying, color separation and quality separation, the raw material is random polypropylene, the transmittance is 72%, the maximum dissolution of n-hexane is 2.5%, the maximum dissolution of xylene is 12%, and the volatile matter is 0.2%, Ganzhou Runshengke Environmental Protection Materials Co., Ltd.; Recycled polypropylene 2: Recycled from transparent chip boxes, after sorting, crushing, friction cleaning, drying, color separation and quality separation, the raw material is obtained, random polypropylene, the transmittance is 75%, the maximum dissolution of n-hexane is 3.5%, the maximum dissolution of xylene is 9.8%, and the volatile matter is 0.23%, Anhui Lianxin New Materials Co., Ltd.; Recycled polypropylene 3: Recycled from transparent lunch boxes, the raw materials are obtained after sorting, crushing, friction cleaning, drying, color separation and quality separation. The light transmittance is 70%, the maximum dissolution of n-hexane is 0.98%, the maximum dissolution of xylene is 15%, and the volatile matter is 0.36%. Hunan Xinjiyuan New Materials Co., Ltd. Nanoporous silicate 1: Specific surface area is 1200m 2 / g, D50 particle size is 32 nm, JH-200A, Ningbo Jiahe New Material Technology Co., Ltd.; Nanoporous silicate 2: Specific surface area is 4050m 2 / g, D50 particle size of 15.3 nm, JH-200B was obtained by grinding JH-200A; Porous structure inorganic silicate: specific surface area is 65m 2 / g, D50 particle size is 3.4 microns, Shanghai Chonghedou; Diatomaceous earth: brand 512, specific surface area 25m 2 / g, D50 particle size is 11.1 μm, purchased from Shanghai Chonghedou New Materials; Zeolite: 4A zeolite powder, D50 particle size 4 microns, specific surface area 83m 2 / gNingbo Jiahe New Material Technology Co., Ltd.; Toughening / clarifying agent 1: ethylene-octene copolymer, POE ENAGE 7467, DowDuPont; Toughening / clarifying agent 2: SEBS, Y-501T, Baling Petrochemical; Toughening / clarifying agent 3: olefin block copolymer, POE LC168, LG Chemical; Toughening / clarifying agent 4: LLDPE EXCEED 3518PA ExxonMobil Anti-precipitation agent: PEP-36, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate, Aidico; Antioxidant: RIANOX 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and RIANOX 168 (tris(2,4-di-tert-butylphenyl) phosphite) in a weight ratio of 1:2, Rianlon; Commercially available secondary antioxidant: P-EPQ (tetrakis-(2,4-di-tert-butylphenyl)-4,4'-biphenyl bisphosphite), Clariant, Switzerland.
[0023] Embodiment and comparative example The preparation method of the recycled polypropylene composite material: according to the ratio, the components are mixed evenly, and granulated by extrusion through a twin-screw extruder, and the screw temperature range is 180-230° C. to obtain the recycled polypropylene composite material.
[0024] Various test methods: (1) Migration test: FDA 21CFR 177.1520, tested using composite particles.
[0025] (2) Volatile matter test: According to GB / T 2918-2018 standard, bake at 105°C for 5 minutes and use infrared to test the volatile matter content.
[0026] (3) Odor test: According to the PV3900 standard, bake at 80℃ for 4h, cool to 60℃, open the lid and smell the odor. A total of 10 odor experts will be asked to take the average score. The scores are divided into 1-6 levels, which are: 1. No odor; 2. Slight odor; 3. Smell but not irritating; 4. Irritating odor; 5. Strong irritating odor; 6. Unbearable.
[0027] (4) Transmittance / haze: The samples were injection molded into square plates with a thickness of 2 mm, and the transmittance and haze were measured using a colorimeter.
[0028] (5) Notched impact strength: Notched impact specimens were injection molded according to ISO 180:2000 and conditioned at 23°C and 50% relative humidity for 16 h before testing the notched impact strength.
[0029] Table 1: Components (parts by weight) of recycled polypropylene composite materials and test results Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Recycled Polypropylene 1 95 95 95 95 Recycled Polypropylene 2 90 Recycled Polypropylene 3 97 Nanoporous silicate 1 0.5 0.3 0.8 0.5 0.5 Nanoporous silicate 2 0.5 Toughening / Transparent Agent 1 4 3 4 Toughening / Transparent Agent 2 8 4 Toughening / Transparent Agent 3 4 Anti-precipitation agent 0.1 0.05 0.2 0.1 0.1 0.1 Antioxidants 0.3 0.2 0.3 0.3 0.3 n-Hexane dissolution content% 3.2 3.5 2.8 3.8 3.5 3.9 Xylene soluble matter content % 9.8 21.3 8.7 8.6 13.3 11.3 Volatile matter test 0.03 0.04 0.01 0.02 0.01 0.03 Smell test 3.2 3.5 3.0 3.8 3.6 3.8 Transmittance, % 73 78 71 76 81 73 Haze 42 45 41 46 38 43 <![CDATA[Notched impact strength, kJ / m 2 > 4.2 5.2 3.8 4.3 5.8 4.8 It can be seen from Examples 1 / 5 / 6 that when SEBS is the preferred toughening agent, the toughness is better, the transparency is higher, the volatile matter is lowest, and the extractables and odor also meet the standards.
[0030] Table 2: Comparative Examples 1-6 Recycled Polypropylene Composite Materials Components (Parts by Weight) and Test Results Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Recycled Polypropylene 1 95 95 95 95 95 95 Nanoporous silicate 1 0.1 1 0.5 Porous structure inorganic silicate 0.5 diatomite 0.5 Zeolite 0.5 Toughening / Transparent Agent 1 4 4 4 4 4 4 Anti-precipitation agent 0.1 0.1 0.1 0.1 0.1 0 Antioxidants 0.3 0.3 0.3 0.3 0.3 0.4 n-Hexane dissolution content% 4.1 4.4 4.1 4.6 3.5 4.0 Xylene soluble matter content % 13.6 10.5 12.2 14.9 8.8 10.2 Volatile matter test 0.16 0.32 0.34 0.17 0.05 0.12 Smell test 4.3 4.3 4.5 4.1 2.8 3.2 Transmittance, % 51 48 43 70 58 56 Haze 67 72 74 63 70 86 <![CDATA[Notched impact strength, kJ / m 2 > 4.2 4.1 3.6 4.3 3.3 4.3 It can be seen from the examples and comparative examples that the addition of nanoporous silicate and anti-precipitation agent can not only effectively reduce the odor, volatility and dissolution of the material, but also improve the light transmittance of the material and reduce the haze, thereby providing a good solution for the development of transparent recycled polypropylene materials.
[0031] Specifically, it can be seen from Comparative Examples 1-3 that the adsorption capacity of inorganic silicates, diatomaceous earth and zeolite using traditional porous structures is insufficient and the transparency is seriously reduced.
[0032] It can be seen from Comparative Example 4 that if the content of nanoporous silicate is too low, the adsorption capacity is insufficient and too many small molecular impurities also lead to increased haze.
[0033] It can be seen from Comparative Example 5 that if the content of nanoporous silicate is too high, the transparency will be significantly reduced.
[0034] It can be seen from Comparative Example 6 that when the anti-precipitation agent of the present invention is not contained, the volatile matter of the recycled polypropylene composite material cannot be effectively suppressed, and the haze is very high, which seriously affects the transparency.
[0035] Table 3: Comparative Examples 7-9 Recycled Polypropylene Composite Components (Parts by Weight) and Test Results Comparative Example 7 Comparative Example 8 Comparative Example 9 Recycled Polypropylene 1 95 95 Recycled Polypropylene 2 90 Nanoporous silicate 1 0.3 0.5 0.5 Toughening / Transparent Agent 1 4 10 Toughening / Transparent Agent 4 8 Anti-precipitation agent 0.05 0.1 Commercially available secondary antioxidants 0.1 Antioxidants 0.2 0.3 0.3 n-Hexane dissolution content% 4.3 4.5 5.6 Xylene soluble matter content % 27.6 12.3 31.8 Volatile matter test 0.16 0.21 0.12 Smell test 3.9 4.2 4.3 Transmittance, % 46 49 46 Haze 58 56 68 <![CDATA[Notched impact strength, kJ / m 2 > 3.4 3.8 6.5 It can be seen from Comparative Example 7 that the transparent toughening agent LLDPE commonly used in polypropylene does not provide sufficient toughening and also significantly affects transparency.
[0036] It can be seen from Comparative Example 8 that other commercially available auxiliary antioxidants, even if their molecular formulas are similar to the anti-precipitation agent of the present invention, cannot improve the transparency and have too high odor and volatile matter.
[0037] It can be seen from Comparative Example 9 that if the toughening / clarifying agent content is too high, the dissolution will increase significantly and the transparency will also decrease significantly, which cannot meet the requirements.
Claims
1. A recycled polypropylene composite material, characterized in that: By weight, it includes the following components: Recycled polypropylene 90-97 parts; Nanoporous silicate 0.3-0.8 parts; 3-8 parts of toughening / transparent agent; Anti-precipitation agent 0.05-0.2 parts; The specific surface area of nanoporous silicate is 1000-10000m 2 / g, D50 particle size is 10-50 nanometers; The anti-precipitation agent is selected from bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate.
2. The recycled polypropylene composite material according to claim 1, characterized in that: The toughening / transparent agent is selected from at least one of ethylene-octene copolymer, olefin block copolymer, and styrene-ethylene-butylene-styrene block copolymer.
3. The recycled polypropylene composite material according to claim 2, characterized in that: The toughening / transparent agent is selected from styrene-ethylene-butylene-styrene block copolymer.
4. The recycled polypropylene composite material according to claim 1, characterized in that: By weight, the invention also includes 0-2 parts of processing aids, wherein the processing aids are selected from at least one of antioxidants, lubricants, ultraviolet absorbers and pigments.
5. The recycled polypropylene composite material according to claim 1, characterized in that: The recycled polypropylene is a random copolymer recycled polypropylene with a 2mm light transmittance greater than 70%.
6. The recycled polypropylene composite material according to claim 1, characterized in that: The recycled polypropylene composite material is tested with reference to the non-cooking standard in FDA 21CFR 177.1520, with the maximum dissolution in n-hexane less than 4%, the maximum dissolution in xylene less than 23%, the volatile matter test less than 0.1%, the light transmittance of a 2 mm thick square plate greater than 70%, and the haze less than 50%.
7. The method for preparing the recycled polypropylene composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder, wherein the screw temperature range is 180-230 DEG C, and obtaining a recycled polypropylene composite material.
8. The use of the recycled polypropylene composite material according to any one of claims 1 to 6, characterized in that: Used for preparing food packaging, medicine packaging, and tableware.
Citation Information
Patent Citations
Low-odor and yellowing resistant polypropylene composition and preparation method thereof
CN103044776A
Modified polypropylene composition and preparation method thereof
CN106009271A
Environment-friendly-low smell vehicle-using polypropylene composite material and preparation method thereof
CN108485066A
Polyolefins compositions obtained from recycled polyolefins
US20230383109A1
Odorless environmentally friendly recycled polypropylene plastic and preparation method therefor
WO2024012475A1
Cited By
Recycled cotton fiber modified polypropylene composite material with fresh scent and soft touch feeling and preparation method of recycled cotton fiber modified polypropylene composite material
CN121673702A